Keterkaitan pengalaman magang dengan kesiapan kerja mahasiswa tingkat akhir: Studi pada jurusan administrasi niaga Politeknik Negeri Bandung - Sintawati, Putri; Tjahjawati, Sri Surjani (Journal of Management and Digital Business, 2025)
Improving labor productivity and competitiveness requires developing high-quality human resources (HR). Education and training, including internship programs, provide direct experience with real-world work practices. The high unemployment rate among university graduates in Indonesia indicates that work readiness remains a key challenge in HR development. This study examines the effect of internship experience on the work-readiness of final-year students in the Business Administration Department at Bandung State Polytechnic, using a quantitative approach with descriptive analysis and SEM-PLS. Data were obtained through questionnaires distributed to 192 students who met the research criteria. The results show that internship experience has a positive, significant effect on students' work-readiness. These findings highlight the importance of internship programs as a strategic effort to develop human resources ready to compete in the job market. Therefore, students are encouraged to make the most of internship programs to develop into more competent, job-ready graduates.